2015
DOI: 10.1074/jbc.m115.641746
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Shows High Affinity Interaction with Voltage-dependent Anion Channel, Suggesting Mechanisms of Mitochondrial Regulation and Toxicity in Parkinson Disease

Abstract: Background:The intrinsically disordered protein ␣-synuclein, a hallmark of Parkinson disease, is involved in mitochondrial dysfunction in neurodegeneration and directly interacts with mitochondria. Results: ␣-Synuclein regulates VDAC permeability; ␣-synuclein toxicity in yeast depends on VDAC. Conclusion: ␣-Synuclein both blocks VDAC and translocates via this channel across the mitochondrial outer membrane. Significance: (Patho)physiological roles of monomeric ␣-synuclein may originate from its interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
191
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(205 citation statements)
references
References 77 publications
4
191
0
3
Order By: Relevance
“…It was recently reported that in addition to tubulin, another abundant cytosolic protein, a neuronal intrinsically disordered α-synuclein involved in etiology of Parkinson disease (PD), effectively blocks VDAC [139]. Rostovtseva et al [139] have shown that monomeric α-synuclein not only reversibly blocks VDAC conductance, similarly to what has been shown to tubulin, but also is able to translocate through the VDAC pore. Experiments with yeast model of PD supported electrophysiological results by demonstrating that VDAC is indeed required for α-synuclein toxicity in yeast.…”
Section: Unsolved Problems In Vdac Structure and Functionmentioning
confidence: 99%
“…It was recently reported that in addition to tubulin, another abundant cytosolic protein, a neuronal intrinsically disordered α-synuclein involved in etiology of Parkinson disease (PD), effectively blocks VDAC [139]. Rostovtseva et al [139] have shown that monomeric α-synuclein not only reversibly blocks VDAC conductance, similarly to what has been shown to tubulin, but also is able to translocate through the VDAC pore. Experiments with yeast model of PD supported electrophysiological results by demonstrating that VDAC is indeed required for α-synuclein toxicity in yeast.…”
Section: Unsolved Problems In Vdac Structure and Functionmentioning
confidence: 99%
“…At higher potentials VDAC exhibits lower conductance and cation-selective states called closed states. However, the channel behavior of reconstituted VDAC is not the same as that of native one located in the mitochondrial outer membrane as several endogenous factors were indicated to modulate VDAC activity, including NADH [63], Ca 2+ [36], tubulin [64,65], tBid [66] and other members of Bcl-2 protein family [67], hexokinase I and II [36], α-synuclein [68], 18 kDa Translocator protein (TSPO) [69,70] as well as mitochondrial lipids [71] and still unidentified cytoplasmic and mitochondrial proteins [72]. As summarized by [73], VDAC interactions with different proteins contribute to apoptosis, cytoskeleton functions, Ca 2+ and oxidative-redox homeostasis as well as energy transformation (Figure 2).…”
Section: Vdac As a Versatile Proteinmentioning
confidence: 99%
“…Intravesicular pH drops along the endocytic pathway to ϳ6 and in late endosomes and lysosomes to as low as 4.5 (25,27). In addition to its role in vesicular fusion and trafficking, ␣S is subject to lysosomal degradation (28), and it may enter the slightly alkaline mitochondrial environment (29). Furthermore, pH dysregulation accompanying oxidative stress can result in cytosolic acidification (30), and oxidative stress is a significant contributor to PD pathology (31).…”
mentioning
confidence: 99%